Resistance Against Corporation by the Religion-Based Environmental Movement in Water Resources Conflict in Pandeglang, Indonesia - M Dian Hikmawan; Ika Arinia Indriyany; Abdul Hamid (Department of Government Studies Universitas Muhammadiyah Makassar, 2021)
Natural resource conflicts between corporations and local communities were quite common in Indonesia. In an area in Pandeglang-Banten, a giant corporation tried to control the natural resources, especially in this case is water resource, and the local religious based community fought against the corporation’s agenda. This paper describes the formation of a religious-based community doing social movement against a big corporation in Pandeglang, Banten Indonesia. The research method uses qualitative with case study strategy. The research location was in Cadasari District, Pandeglang Regent, Banten Province, Indonesia. This paper shows that the social movement succeeded to defend their accesses to water resources through religious doctrine easily understood by local people under the leadership by the local religious leaders (Kyai) from local Islamic schools (Pesantren). They share collective identity, as victims of the company project and also a moslem. The collective identity as victims as well as moslems, linked by dense religious informal networks and corporation and local government as clear enemy made their movement successfully terminated the company project. As a main actor, Kyai played significant roles to mobilize people in this social movement. Using her charismatic character, Kyai was able to defeat legal-rational leadership such as local government and security forces.